The dance of macrophage death: the interplay between the inevitable and the microenvironment - Makuch, Magdalena; Stepanechko, Mariia; Bzowska, Małgorzata (Frontiers in Immunology, 2024)
Macrophages are highly plastic cells ubiquitous in various tissues, where they perform diverse functions. They participate in the response to pathogen invasion and inflammation resolution following the immune response, as well as the maintenance of homeostasis and proper tissue functions. Macrophages are generally considered long-lived cells with relatively strong resistance to numerous cytotoxic factors. On the other hand, their death seems to be one of the principal mechanisms by which macrophages perform their physiological functions or can contribute to the development of certain diseases. In this review, we scrutinize three distinct proinflammatory programmed cell death pathways pyroptosis, necroptosis, and ferroptosisoccurring in macrophages under specific circumstances, and explain how these cells appear to undergo dynamic yet not always final changes before ultimately dying. We achieve that by examining the interconnectivity of these cell death types, which in macrophages seem to create a coordinated and flexible system responding to the microenvironment. Finally, we discuss the complexity and consequences of pyroptotic, necroptotic, and ferroptotic pathway induction in macrophages under two pathological conditionsatherosclerosis and cancer. We summarize damage-associated molecular patterns (DAMPs) along with other microenvironmental factors, macrophage polarization states, associated mechanisms as well as general outcomes, as such a comprehensive look at these correlations may point out the proper methodologies and potential therapeutic approaches.